Problem solving training: intervention in depressed women - Cade, Nágela Valadão; Prates, José Gilberto (Revista da Escola de Enfermagem da USP, 2001)
This is an exploratory and descriptive study which has aimed from the Problem Solving Training accomplished in 12 group sessions with women admitted to hospital suffering from depression, to evaluate the effect of this intervention. BECK Depression Scale, SPILBERGER Anxiety State Scale, MCKAY Problem List, a Written Simulation Exercises about coping in five situations and an interview about the perception of group participation were used for the assessment of the patients. It was concluded that the training had positive effects about the women as for the technique used as for the communication established and for group therapeutic factors which appeared in this scenery.